Plant species richness and shrub cover attenuate drought effects on ecosystem functioning across Patagonian rangelands - Gaitan, Juan Jose; Bran, Donaldo Eduardo; Oliva, Gabriel Esteban; Maestre, Fernando Tomás; Aguiar, Martín Roberto; Jobbagy Gampel, Esteban Gabriel; Buono, Gustavo Gabriel; Ferrante, Daniela; Nakamatsu, Viviana Beatriz; Ciari, Georgina; Salomone, Jorge Manuel; Massara Paletto, Virginia (2017)
Drought is an increasingly common phenomenon in drylands as a consequence of climate change. We used 311 sites across a broad range of environmental conditions in Patagonian rangelands to evaluate how drought severity and temperature (abiotic factors) and vegetation structure (biotic factors) modulate the impact of a drought event on the annual integral of normalized difference vegetation index (NDVI-I), our surrogate of ecosystem functioning. We found that NDVI-I decreases were larger with both increasing drought severity and temperature. Plant species richness (SR) and shrub cover (SC) attenuated the effects of drought on NDVI-I. Grass cover did not affect the impacts of drought on NDVI-I. Our results suggest that warming and species loss, two important imprints of global environmental change, could increase the vulnerability of Patagonian ecosystems to drought. Therefore, maintaining SR through appropriate grazing management can attenuate the adverse effects of climate change on ecosystem functioning.